Design and detection of hardware Trojan based on satisfiability don't cares - Lingjuan WU; Jiacheng ZHU; Shibo TANG; Jing TAN; Wei HU (网络与信息安全学报)
Hardware Trojans are intended malicious design modifications to integrated circuits, which can be used to launch powerful low-level attacks after being activated.A new security threat of lightweight stealthy hardware Trojans leveraging discrete satisfiability don't care signals was demonstrated.These don't care could not be satisfied under normal operation and thus the circuit design with Trojan is functionally equivalent to the Trojan-free baseline.The attacker could activate the Trojan through simple yet effective fault injection.Experimental results on a 1024-bit RSA cryptographic core show that the proposed hardware Trojan can escape from logic synthesis optimization, and that the RSA private key can be retrieved by simply over-clocking the design.A defense technique that can effectively detect such stealthy Trojan design was provided.